The Relationships Among Maternal Meta-emotion Philosophy, Maternal Video-Mediated Cognitions, and Adolescent Behavior Adjustment in Taiwan. - Chang, Hui-Tzu; Liu, Yih-Lan; Kuo, Chao-Sheng (Child Psychiatry & Human Development, 2023)
This study examines the relationships among maternal meta-emotion philosophy, maternal video-mediated cognitions, and adolescent behavior adjustment. We adopt video-mediated recall methods to obtain mothers' perceptions of their interaction with their children. In total, 121 pairs of mothers (age, M = 42.55) and their adolescent children (age, M = 12.34) were videotaped for 10 min while discussing daily issues. The mothers reviewed the tape (30 episodes) and rated their own behaviors and the counterparts' behaviors on 8 cognitive or affective dimensions. The mothers also completed a parental meta-emotion philosophy inventory, and the adolescents completed the Youth Self-Report. The results indicate that maternal emotional dysfunction has a positive effect on adolescents' externalizing problem behaviors through mothers' perceptions of conflictual interaction. These findings highlight the importance of considering maternal meta-emotion philosophy in the mother-adolescent interaction process and understanding adolescent problem behaviors.